2020
DOI: 10.1002/mar.21412
|View full text |Cite
|
Sign up to set email alerts
|

“Minor crimes” against wildlife: Small offenses, lasting impact, and a proposed solution

Abstract: Past research has examined why people engage in negative consumer behaviors, but research has not adequately examined what drives minor crimes against wildlife, which is important given their prevalence and impact on the welfare of wildlife. We address this need for research with two studies that examine minor crimes against wildlife in the context of wildlife jams (i.e., traffic jams caused by wildlife in and around roadways that obstruct the normal flow of traffic). Study 1 introduces a research methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The study area for this paper is Nyerere National Park in Tanzania. Nyerere National Park is selected due to its tourism potential, and also according to Tanzania National Parks Source Findings Alamsyah and Wardi (2020) Engagement as a dimension of measuring enjoyment Blomstervik et al (2020) Novelty in tourism national parks for international and domestic tourists with mostly female educated with university education Boonpat and Suvachart (2014) Direct experiences from tourism cultural perspective Japutra and Keni (2020) Image as a fulfillment for tourists Lin et al (2008) Engagement as a dimension of measuring enjoyment Minton et al (2020) Negative effects of national parks Mkwizu ( 2018 In tourists' memorable experiences there was positive effect between visitor engagement and e-word of mouth in heritage sites Snyman et al (2023) Positive linkage between national parks and development Xu and Chan (2009) Direct experiences through evaluation of goods and services Note(s): Source and Findings Table 1.…”
Section: Research Context and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The study area for this paper is Nyerere National Park in Tanzania. Nyerere National Park is selected due to its tourism potential, and also according to Tanzania National Parks Source Findings Alamsyah and Wardi (2020) Engagement as a dimension of measuring enjoyment Blomstervik et al (2020) Novelty in tourism national parks for international and domestic tourists with mostly female educated with university education Boonpat and Suvachart (2014) Direct experiences from tourism cultural perspective Japutra and Keni (2020) Image as a fulfillment for tourists Lin et al (2008) Engagement as a dimension of measuring enjoyment Minton et al (2020) Negative effects of national parks Mkwizu ( 2018 In tourists' memorable experiences there was positive effect between visitor engagement and e-word of mouth in heritage sites Snyman et al (2023) Positive linkage between national parks and development Xu and Chan (2009) Direct experiences through evaluation of goods and services Note(s): Source and Findings Table 1.…”
Section: Research Context and Designmentioning
confidence: 99%
“…(2023) indicates the positive side of national parks. On the other hand, Minton, Sisneros-Kidd, and Monz (2020) concentrated on wildlife with much concern on negative effects of national parks such as safety rather than enjoyment of national parks. In fact, Mkwizu (2018), Mogomotsi et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is important to provide reliable and generalized knowledge to improve the ecology of research (Van Heerde et al , 2021) and understand how consumers, organization or policymakers can help achieve the sustainable development goals. Field experiments (Grazzini et al , 2018), field observations (Minton et al , 2020), (N)ethnography (Herjanto et al , 2021) and secondary data (D’Lima et al , 2018) can all complement the package of studies. This does not mean we should neglect the utility of online or laboratory studies.…”
Section: Contribution To Sustainable Development Goalsmentioning
confidence: 99%
“…Consumptive recreation activities, such as hunting, bring direct change to wildlife populations, whereas nonconsumptive recreational activities, such as skiing, do not intend to exert the same direct impact on the environment (Minton et al, 2020). However, researchers have identified that nonconsumptive recreational activities may also result in negative impacts on wildlife and the resultant environment (Blanc et al, 2006; Larson et al, 2016; Olsen, 2022).…”
Section: Introductionmentioning
confidence: 99%